2023
DOI: 10.1051/0004-6361/202142141
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of rocky planets formed by rapid pebble accretion

Abstract: We present a series of papers dedicated to modelling the accretion and differentiation of rocky planets that form by pebble accretion within the lifetime of the protoplanetary disc. In this first paper, we focus on how the accreted ice determines the distribution of iron between the mantle (oxidized FeO and FeO1.5) and the core (metallic Fe and FeS). We find that an initial primitive composition of ice-rich material leads, upon heating by the decay of 26Al, to extensive water flow and the formation of clay min… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 109 publications
0
5
0
Order By: Relevance
“…Nonetheless, these iron-meteorite parent bodies have relatively small core mass fractions, an average of 21% for NC-iron cores and 13% for CC-iron cores ( 31 ), compared with those of terrestrial planets: Mars at 25% ( 77 ) and Earth at 32.5% ( 78 ). If the iron-meteorite parent bodies are representative of initial accretion materials for terrestrial planets, later accretion of highly reduced materials (such as metal-rich pebbles) is needed to account for the relatively high core mass fractions of Mars and Earth ( 79 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, these iron-meteorite parent bodies have relatively small core mass fractions, an average of 21% for NC-iron cores and 13% for CC-iron cores ( 31 ), compared with those of terrestrial planets: Mars at 25% ( 77 ) and Earth at 32.5% ( 78 ). If the iron-meteorite parent bodies are representative of initial accretion materials for terrestrial planets, later accretion of highly reduced materials (such as metal-rich pebbles) is needed to account for the relatively high core mass fractions of Mars and Earth ( 79 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact CMB temperature increase varies in different MGI models, it should be higher than that resulting from the core‐formation process during previous smaller impacts (Nimmo, 2022). Pebble accretion may also increase CMB temperatures, while recent studies suggest this mechanism is so efficient that it could melt the entire mantle (e.g., Johansen et al., 2023), leaving no solid mantle to produce strong mantle plumes. Our results show that the unique context caused by the MGI can give rise to strong mantle plumes capable of inducing subduction even when the maximum lithosphere yield strength is >150 MPa, which is noticeably higher than inversions based on present‐day plate tectonics (Rudi et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In Paper I of this series (Johansen et al 2023a), we demonstrated how planetesimals forming outside the ice line melt and desiccate through heat release by the decay of 26 Al. Energy from the decay of 26 Al runs out after a few half-lives (t 1/2 = 0.7 Myr).…”
Section: Introductionmentioning
confidence: 97%